2017
DOI: 10.15835/buasvmcn-vm:12591
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Aspects and Differential Diagnosis of the Cutaneous Round Cell Tumors in Dogs

Abstract: Round cell neoplasms (RCNs) are frequent cutaneous lesions in dogs, with high percentages among skin tumors. In this category are included histiocytoma, mast cell tumor, plasmacytoma, lymphoma and transmissible venereal tumor. The aim of the study was to perform an epidemiological study with reference to the cutaneous round cell tumors in a period of 10 years in the Department of Pathology (Faculty of Veterinary Medicine, ClujNapoca, Romania). Additionally, in the recorded cases with round cell tumors (mast ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…Concerning age at diagnosis, in our study, MCT were diagnosed on an average age of 8.38 years old which is consistent with former studies 6,16,18,23,26,27,[29][30][31] although one study found average age being older (around 11 years old). 15 Also, our results analysing differences in age depending on the grade of MCT were similarly consistent with other studies 23,29 in that the proportion of high grade MCT increases with advancing age. In this regard, the previously described aging of the canine population in our region could explain, at least partially, why we obtained smaller proportion of grade 1 MCT (3.4%) and higher ones of grade 2 MCT (86.5%), when compared with previous works 6,14,19,23,30,34 that obtained results ranging from 12.9% to 33.3% for grade 1 and from 33.6% and 76.3% for grade 2.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Concerning age at diagnosis, in our study, MCT were diagnosed on an average age of 8.38 years old which is consistent with former studies 6,16,18,23,26,27,[29][30][31] although one study found average age being older (around 11 years old). 15 Also, our results analysing differences in age depending on the grade of MCT were similarly consistent with other studies 23,29 in that the proportion of high grade MCT increases with advancing age. In this regard, the previously described aging of the canine population in our region could explain, at least partially, why we obtained smaller proportion of grade 1 MCT (3.4%) and higher ones of grade 2 MCT (86.5%), when compared with previous works 6,14,19,23,30,34 that obtained results ranging from 12.9% to 33.3% for grade 1 and from 33.6% and 76.3% for grade 2.…”
Section: Discussionsupporting
confidence: 92%
“…We found male dogs to be at a greater risk of HCT which is adds to the discordance in the literature about the relevance of sex to this tumour type. 15,41 Our results for sex as a factor risk for PLA revealed no differences in risk due to sex for this tumour type, although the only reference to compare with found a greater proportion of males versus female dogs in a sample of 49 dogs suffering from PLA. 36,37 Finally, when comparing the results obtained in different islands, we saw a lower risk in all islands when compared with Gran Canaria although this is mostly due to an overrepresentation of cases submitted from Gran Canaria to the APDS as explained below.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The expression of CD117 in cytoplasm was observed in 64.29% of high-grade malignancy mast cell tumors, while mutations of c-KIT proto-oncogene were not found in tumor samples from dogs with mast cell tumor [24,25]. Roundcell tumors are among the most common cutaneous tumors, and the established distribution of mast cell tumor, histiocytoma and lymphoma are close to the results presented by other authors [26].…”
Section: Discussionsupporting
confidence: 75%